(untitled) (ALPHA. Journal of Arts, Literature and Philosophy, 2019)
The theoretical strategies of the zapatista movement in Chiapas, express zapatismo’s simultaneous self-determined inscription in Western thought, and its markedly non-Western conceptualization of liberation and structural [epistemological] criticism. This investigation examines how the role of community experience in zapatista theory and praxis, allows zapatismo to overcome the “pluralism” of the current era of global capitalism and postmodern relativism and establish a paradigm for anti-capitalist and anti-neoliberal struggles throughout the world